2020
DOI: 10.1007/s00248-020-01639-x
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Nitrogen-Cycling Microbial Genes in a Waste Stabilization Pond Reveals Changes over Space and Time that Is Uncoupled to Changing Nitrogen Chemistry

Abstract: Nitrogen removal is an important process for wastewater ponds prior to effluent release. Bacteria and archaea can drive nitrogen removal if they possess the genes required to metabolize nitrogen. In the tropical savanna of northern Australia, we identified the previously unresolved microbial communities responsible for nitrogen cycling in a multi-pond wastewater stabilization system by measuring genomic DNA and cDNA for the following: nifH (nitrogen fixation); nosZ (denitrification); hzsA (anammox); archaeal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Meanwhile, the reaction of sulfur cycle that occurs in bio-system is essential for sulfur-containing odorous gases elimination [47]. In our study, a large number of homologous genes referring to each key gene were identi ed by metagenomic sequencing, suggesting the diversity of nitrogen-cycling microbial genes [46,48]. Signi cantly changes in relative abundance of nitrogen-and sulfur-cycling related genes indicated an activated nitrogen and sulfur metabolisms in our bio lter.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Meanwhile, the reaction of sulfur cycle that occurs in bio-system is essential for sulfur-containing odorous gases elimination [47]. In our study, a large number of homologous genes referring to each key gene were identi ed by metagenomic sequencing, suggesting the diversity of nitrogen-cycling microbial genes [46,48]. Signi cantly changes in relative abundance of nitrogen-and sulfur-cycling related genes indicated an activated nitrogen and sulfur metabolisms in our bio lter.…”
Section: Discussionmentioning
confidence: 60%
“…Complex metabolic networks containing a number of key genes have been revealed in different microbes [45]. NH 4 − ion assimilation involves a nitrogen-cycling consisted of several key genes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, reaction of sulfur cycle that occurs in bio-system is essential for the elimination of sulfurcontaining odorous gases [47]. In our study, a large number of homologous genes referring to each key gene were identi ed by metagenomic sequencing, giving us an opportunity to screen novel nitrogencycling microbial genes [46,48]. Signi cantly changes in relative abundance of nitrogen-and sulfurcycling related genes indicated an important role of nitrogen and sulfur metabolisms in odorous gas removal.…”
Section: Discussionmentioning
confidence: 87%
“…Complex metabolic networks containing a number of key genes have been revealed in different microbes 46 . NH 4 − ion assimilation involves a nitrogen-cycling consisted of several key genes 47 . Meanwhile, reaction of sulfur cycle that occurs in bio-system is essential for the elimination of sulfur-containing odorous gases 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, reaction of sulfur cycle that occurs in bio-system is essential for the elimination of sulfur-containing odorous gases 48 . In our study, a large number of homologous genes referring to each key gene were identified by metagenomic sequencing, giving us an opportunity to screen novel nitrogen-cycling microbial genes 47 , 49 . Significantly changes in relative abundance of nitrogen- and sulfur-cycling related genes indicated an important role of nitrogen and sulfur metabolisms in odorous gas removal.…”
Section: Discussionmentioning
confidence: 99%